Análisis comparativo in vitro del grado de microfiltración marginal entre iónomeros de vidrio de fotocurado vs iónomeros de vidrio de autocurado. - Carrión Cueva, Thalía Ivonne (2016)
The general objective of this in vitro study was to determine the degree of marginal microleakage with glass ionomer restorations photo curing vs. self-curing glass ionomer. The study conducted in this research was quantitative, experimental, and comparative. It was sampled 60 healthy human premolars extracted by therapeutic indication during the period March to July 2016, which were submitted using a standardized cleaning and cavity, restoration preparation protocol (as specified by the manufacturer), classification of the sample into four groups: Group A self-curing ionomer (GC Gold Label Glass Ionomeer Universal Restorative), Group B self-curing ionomer Ketac Molar Easymix, Group C curing ionomer (GC Glass Ionomer Light-Cured Universal Restorative), Group ionomer light-cured (Voco Ionolux), these were subjected to an aging process and test microfiltration, Then longitudinal cuts were made in the restoration and proceeded to measure the degree of microfiltration in values from 0 = absence of microfiltration microfiltration 4mm all while the curing glass ionomer have less microfiltration. Keywords: self-curing glass ionomer, glass ionomer curing, marginal microfiltration restoration.